Analisis Faktor yang Memengaruhi Minat Belajar Pendidikan Agama Islam pada Siswa: Studi Kasus di SMA Daruttaqwa Dahanrejo Kebomas Gresik - Muhammad Misbahul Nursajidin; H.Mustadi; Anak Agung Putu Agung (Jurnal Budi Pekerti Agama Islam, 2026)
This study aims to examine the factors that influence students’ interest in learning Islamic Religious Education (PAI) at SMA Daruttaqwa Dahanrejo Kebomas Gresik. The research applies a qualitative method using a case study approach. Data collection was carried out through in-depth interviews with students, teachers, and administrative staff, as well as direct observation of the PAI learning process. The results reveal that students’ learning interest is shaped by both internal and external factors. Internal factors include individual characteristics, intellectual ability, and psychological conditions. Meanwhile, external factors consist of the role of competent teachers, parental support, the availability of facilities and infrastructure, and a supportive learning environment. The implementation of PAI learning involves various methods, such as lectures, storytelling of prophets and pious scholars, question-and-answer activities, the use of social and visual media, assignments, discussions, and role modeling. Factors that enhance learning interest include teacher motivation, family support, a conducive environment, alignment with students’ interests, and the quality of learning materials. The primary obstacle identified is the suboptimal management and scheduling of instructional time.